AB0716 Some Causes for Delayed Recognition of Ankylosing Spondylitis in Real Clinical Practice in Russia: Results of A Single Multicenter Non-Interventional Study – Epika 2. (15th July 2016) - Erdes, S.; Dubinina, T.; Rumyantseva, O.; Abdulganieva, D.; Vinogradova, I.; Evstigneeva, L.; Yelonakov, A.; Otteva, E.; Raskina, T.; Salnikova, T.; Samigullina, R.; Sorotskaya, V.; et al.
Abstract : Objectives: Recognition of ankylosing spondyloarthritis (AS) in current real clinical practice is often delayed. Identification of main causes of this peculiarity would help to propose administrative interventions to improve practices. Methods: A single multicenter non-interventional study was conducted in spring 2015 y in order to ascertain the clinical features of AS in the real practice of a rheumatologist. 402 consecutive AS pts (meeting modified N-Y criteria) referred to a rheumatologist were evaluated following accepted standards during 2 mo at 10 clinical centers of Russia. All pts were evaluated, including those who attended because of deterioration, and pts coming for scheduled check-ups within the disease monitoring program. Patients' mean age was 40, 8±11, 5 y, . 292 (72, 6%)- males, 82, 6% were HLA-B27- positive. Results: Time to establishing the AS diagnosis from the disease onset was 85, 2±86, 2 mo. In 32, 3% of cases the diagnosis was made within 2 years from the onset, in 52, 5% - within 5 years, and in 25, 8% of pts the diagnosis was established in >10 years after AS onset. Association with specific clinical AS features at disease onset, such as axial or joint involvement (location, spatial extent of pain and synovitis) was not established. The AS diagnosis in 351 (87, 3%) pts was established by rheumatologist, in 25 (6, 2%) – by general practitioner, in 14 (3, 5%) – by neurologist, and in remaining pts – by other specialists. During the first reference to a doctor the AS diagnosis was established in 3, 7% (15 pts) cases, during 2–5 visits – in 25, 1% (101), during 6–10 visits – in 25, 1% (113), while 43, 0% (173) of cases required >10 visits to establish the AS diagnosis. Probably due to established practices and pts' mentality in Russia all cases with back pain would be referred initially to neurologists and GPs, and only after multiple visits they may be referred to rheumatologists, which explains the fact of establishing AS during the first visit by neurologists and GPs, and only 6% input in AS verification from rheumatologists during Visits 2–5–6%. Generally before recognizing AS physicians were inclined to name it as spine degenerative disease (58%), reactive arthritis (21%), hernia of inter-vertebral disk (34%), osteoarthritis (6%), non-differentiated arthritis (10%), and oths. In almost half (42%) cases pts had to undergo 2–3 other diagnoses (not associated with spondyloarthritis) before AS was verified. Conclusions: In real clinical practice the final AS diagnosis is usually established in 7 years average after AS onset. Pts are usually attended for quite a long period of time by other specialists, who are not sufficiently familiar with AS, therefore, AS is missed and other disease are being treated instead. Therefore, GPs and neurologists require improved and adjusted training, enabling them to suspect AS and timely refer a patient to a rheumatologist. Disclosure of Interest: None declared